What is Johansonia? - P.W. Crous; R.W. Barreto; A.C. Alfenas; F. Rafael; J.Z. Groenewald (IMA Fungus)
The bitunicate ascomycete genus Johansonia is presently treated as a member of Saccardiaceae, a family regarded as incertae sedis within the Ascomycota. Recent collections on leaves of a leguminous host, Dimorphandra mollis, in Mato Grosso, Brazil, led to the discovery of a new species of Johansonia, described here as J. chapadiensis. Based on DNA sequence data of the nuclear ribosomal DNA (LSU), Johansonia is revealed to represent a member of Dothideomycetes, Capnodiales. Although its family could not be resolved, it clustered basal to Schizothyriaceae and Mycosphaerellaceae, and could well represent a species of Saccardiaceae. DNA sequence data of other members of Saccardiaceae would be required, however, to confirm this classification.